SDOF STRUCTURE RESPONSE DUE TO SINUSOIDAL LOADS USING NUMERICAL METHODS (Eternitas: Jurnal Teknik Sipil, 2025)
Dynamic loads are types of loads that change in magnitude and/or direction with time. Structures that frequently experience dynamic loading can receive repeated (periodic) loads. This repetitive load pattern can be in the form of a graph of a sine function or cosine function, therefore the structure needs to be evaluated against dynamic loads with a sinusoidal pattern. The aim of this research is to determine the maximum response of a structure that can be modeled as a single degree of freedom system due to sinusoidal loads. The method used in this research is a numerical method. Based on the results and analysis of the response of the SDOF structure in this research, both Linear Acceleration and Average Acceleration methods show the same results. From the results and analysis it can be concluded that the greater the mass, the greater the maximum displacement produced or in other words the mass is directly proportional to the maximum displacement. This is different from stiffness, the greater the stiffness, the smaller the maximum displacement produced, or in other words, stiffness is inversely proportional to maximum displacement. Variations in mass and stiffness produce maximum velocities whose values are all negative. This shows that the maximum speed occurs in the direction opposite to the direction of the load. The speed and acceleration values for each additional mass tend to increase, while the speed values for each additional stiffness tend to decrease.
Keywords: Structural Response, Newmark Method, Sinusoidal Loading, Mass, Stiffness